Unceratainty of Heisenberg in Universe Destruction - Sri Jumini (International Journal of Science and Applied Science: Conference Series, 2017)
The Qur'an is a guidence which explaines all about the universe to human being. The discovery of science has been able to explain the truth of the Qur'an scientifically. One of which is the principle of Heisenberg's uncertainty in the event of the universe destruction. The purpose of this research is to know: 1) Science's view of the event of the universe destruction (Big Crunch) in Qur’an [Al Infithaar]: 1-3, and How the relation of Heisenberg’s uncertainty principles and the law of thermodynamics II toward  the collapse of the universe (Big Crunch) based on Scientific views and the Quran. This research is a qualitative research using library research method which analyzes the related books directly or indirectly. The results of the analysis stated that: 1) The concentration of mass, which is big enough, relates to some of the laws of physics, those are: Relativity, Heisenberg's uncertainty principles, and the law of Thermodynamic II; 2) The universe will return at its sole point, i.e; the absence of the universe; 3) The destruction of the universe is the destruction of the order of the universe which then the stars fall scatteredly because of the gravitational force that prevents them disappears, the balance of the universe diminishes, decreases and becomes uncertain, and eventually disappears.